2019
DOI: 10.1007/s12598-019-01350-y
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-stable metal nano-catalyst synthesis strategy: a perspective

Abstract: Supported metal nanoparticles (NPs) as an important heterogeneous catalyst have been widely applied in various industrial processes. During the catalytic reaction, size of the particles plays an important role in determining their catalytic performance. Generally, the small particles exhibit superior catalytic activity in comparison with the larger particles because of an increase in lowcoordinated metal atoms on the particle surface that work as active sites, such as edges and corner atoms. However, these sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 87 publications
0
19
0
Order By: Relevance
“…The sintering of catalyst particles reduced the number of active sites, which is responsible for the performance decay under reaction conditions. It is well known that smaller nanoparticles possess higher surface free energy and lower Tammann temperatures, leading to a stronger tendency of agglomeration [47][48][49]. However, it was found that the stability of SP-2 under photothermal catalytic conditions was mildly improved but at the expense of decreased activity.…”
Section: Resultsmentioning
confidence: 99%
“…The sintering of catalyst particles reduced the number of active sites, which is responsible for the performance decay under reaction conditions. It is well known that smaller nanoparticles possess higher surface free energy and lower Tammann temperatures, leading to a stronger tendency of agglomeration [47][48][49]. However, it was found that the stability of SP-2 under photothermal catalytic conditions was mildly improved but at the expense of decreased activity.…”
Section: Resultsmentioning
confidence: 99%
“…On this hand, NAs are designed to avoid these effects and improve recyclability and stability [50]. In particular, the hollow silica capsules efficiently protect the core catalyst from coalescence phenomena by simply acting as a physical shield [7]. NAs, mcNAs, and scNAs do not display significant morphologic changes after the catalytic tests.…”
Section: Formic Acid Catalytic Decompositionmentioning
confidence: 99%
“…Indeed, NPs can be affected by sintering/stability and recovery issues [6]. An elegant strategy to both reduces NPs sintering while increasing their lifetime is the core@shell design, in which the active part is confined in the core and an external shell protect the catalyst [7]. This approach has the intrinsic advantage to increase the NPs recyclability and stability to coalescence due to the protective shell [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The precise nanofabrication is of great significance in both fundamental research and practical applications. The past few decades have witnessed a remarkable progress in the synthesis of zero-, one-, and two-dimensional nanomaterials (Chiu et al, 2011;Cao et al, 2020;Wang et al, 2020), which have aroused widespread interest due to the fascinating size/figure-dependent properties. During a variety of nanostructures, ringlike architectures exhibit novel properties with ring cavities and present promising application prospects in catalysis, sensors, energy storage, and advanced optical/electric nanodevices (Chen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%